Towards a critical politics of translation: (Re)Producing hegemonic climate governance. (December 2018) - Machen, Ruth
This paper raises critical questions about the relationship between knowledge translation and hegemonic power, and the way that this relationship shapes particular forms of neoliberal climate governance. The process of making scientific knowledge meaningful for policy audiences is increasingly being described as knowledge translation (over knowledge transfer or knowledge exchange), but what process does the language of translation describe? What discursive work is performed? And what politics does this shift in language serve? Through detailed analysis of a science–policy boundary organisation in Scotland, the paper examines the way in which emphasis on knowledge translation is central to creating a "demand-led" model of science–policy interaction. Drawing from Laclau and Mouffe's work on articulation, the paper demonstrates the discursive work that translation performs in facilitating the construction and circulation of particular forms of scientific knowledge that (re)produce neoliberal climate change discourses and neoliberal modes of policy delivery. The paper further develops this argument by unpacking science–policy translation as a hegemonic practice. It concludes by calling for greater critical awareness of the hegemonic politics performed through science–policy translation, and highlights key implications – for boundary work, for knowledge politics and for addressing climate change.